The Effect of Work Motivation and Work Orientation on Employee Performance at the Education Office of Central Tapanuli Regency - Margaretha Lubis; Mansur Tanjung; Dicky Syahputra Lubis (Devitara Innovations, 2025)
This study aims to determine the effect of work motivation and work orientation on employee performance at the Education Office of Central Tapanuli Regency. This research used a quantitative method with a descriptive approach. The population in this study consisted of all employees at the Education Office of Central Tapanuli Regency, with a sample of 56 respondents obtained through a total sampling technique. Data were collected through questionnaires and analyzed using correlation analysis, coefficient of determination, and hypothesis testing with t-test and F-test. The results showed that there was a strong relationship between work motivation and employee performance with a correlation coefficient of 0.729, while the relationship between work orientation and employee performance was 0.682. The coefficient of determination analysis showed a value of 0.631, indicating that work motivation and work orientation simultaneously explain 63.1% of the variation in employee performance, while the remaining 36.9% is influenced by other factors not examined in this study. The t-test results indicate that work motivation (t-count 4.887 > t-table 1.67356) and work orientation (t-count 3.787 > t-table 1.67356) have a positive and significant effect on employee performance. Furthermore, the F-test results show that work motivation and work orientation simultaneously have a significant effect on employee performance with an F-count of 45.381 > F-table 3.17 and a significance level of 0.000 < 0.05.